FEATURES OF TAXATION OF INCOME OF NATURAL PERSONS - HORDIEIEVA-HERASYMOVA, Liudmyla; KRAINIAK А. (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Tax revenues to the budget are the main source of filling its revenue part, which, in turn, is an important tool for the implementation of the country’s social and economic policy. Both regional development and the effectiveness of the country’s implementation of its functions depend on the ability to attract a sufficient amount of money to the budgets of different levels. Among the entire set of taxes and fees introduced in Ukraine, one of the leading places in filling the budget belongs to personal income tax. Among the entire set of taxes and fees established in Ukraine, one of the leading places in filling the budget belongs to the personal income tax. Its role in the economy is difficult to overestimate, because it is in the sphere of interests of the entire economically active population of the country. With the help of this tax, the state can have a direct influence on the level of received income and savings of citizens. The principles of personal income taxation should meet the requirements of reducing social contradictions in society, encourage taxpayers to behave honestly towards the obligation to pay taxes. In the conditions of the reform processes that have been actively taking place in the economy of our country in recent years, a number of changes were made to the mechanism of personal income taxation. Currently, there is a need to review the achieved results in order to determine the future course of action. The article is devoted to the issue of personal income taxation, its role in the formation of the revenue part of the state budget. Four key historical stages of reforming the tax system of Ukraine in the aspect of personal income taxation are identified on the basis of studying the regulatory legal acts that were in force in different periods of time. The current state of the transfers of personal income tax and the peculiarities of its administration are analyzed. The trends of personal income tax receipts to local budgets are familiarized. It was found that personal income taxation is one of the main fiscal levers, which determines the impact on ensuring the successful functioning of the economy of our country. Taking into account the experience of the EU countries, directions for further improvement of the mechanism of personal income taxation, which will contribute to the strengthening of the principle of social justice are outlined.